Mesenchymal stem cells transplantation in the treatment of tendon disorders - Adrian Różycki; Michał Pniak; Paweł Miklis; Maciej Mawlichanów; Aleksandra Ciesielska; Aleksandra Sieradzka; Krzysztof Szerej; Alicja Kot; Marta Wojtczak; Natalia Myśliwiec (Quality in Sport)
Introduction and purpose: